La condition des pensionnés de la marine de guerre britannique au xixe siècle - Tri Tran (Cahiers Victoriens et Edouardiens)
From the 17th to the 19th century the Royal Navy was one of Britain’s largest employers, though the number of men serving in the navy contrasted significantly between times of war and peace. A career in the Navy was popular. Anyhow a careful scrutiny of the condition of the sailors and their officers reveals a striking paradox: although the Navy was given considerable financial resources by the government with a view to protecting Britain’s strategic and economic interests, it seems that the majority of naval pensioners underwent financial hardship and distress. Testimonies in primary sources indicate that many lived below the poverty line. Using unpublished archives, this contribution attempts to explain this paradoxical situation by assessing the condition of retired sailors and by showing the evolution of the systems of promotion and retirement in use in the Navy in the Victorian age.